Skeletal muscle metabolism on whole-body positron emission tomography during pitching - Yasushi Takata; Junsuke Nakase; Anri Inaki; Takafumi Mochizuki; Kengo Shimozaki; Kazuki Asai; Seigo Kinuya; Hiroyuki Tsuchiya (Journal of the International Society of Sports Nutrition, 2021)
Background Electromyography (EMG) has been used for evaluating skeletal muscle activity during pitching. However, it is difficult to observe the influence of movement on skeletal muscle activity in deep-lying regions of the trunk and extremities using EMG. An alternative method that may be used is the measurement of glucose metabolism of skeletal muscle using positron emission tomography-computed tomography (PET-CT). This technique is a reliable measure of muscle metabolism, demonstrating a high correlation with the intensity of muscle activity. This study aimed to evaluate whole-body skeletal muscle metabolism during pitching using PET-CT. Methods Ten uninjured, skilled, adult pitchers, who were active at college or professional level, threw 40 baseballs at maximal effort before an intravenous injection of 37 MBq of 18F-fluorodeoxyglucose (FDG). Subsequently, additional 40 balls were pitched. PET-CT images were obtained 50 min after FDG injection, and regions of interest were defined within 72 muscles. The standardized uptake value (SUV) of FDG by muscle tissue per unit volume was calculated, and the mean SUV of the pitchers was compared with that of a healthy adult control group who did not exercise before the measurements. Statistical analysis was performed using a t-test, and P < 0.05 was considered statistically significant. Results Whole-body PET images showed a significant increase in glucose metabolism in the muscle groups of the fingers and toes in both the throwing and non-throwing sides. Additionally, asymmetric increases in glucose metabolism were observed in the muscles of the thigh. Conclusions This is the first study to evaluate whole-body muscle metabolism during pitching using PET-CT. Our findings would be useful in determining the training required for pitchers, and can be further applied to other sporting activities that involve throwing.